Molecular Characterization of Cryptosporidium Isolates Obtained from Humans in France - Guyot, K. (American Society for Microbiology, 2001)
Cryptosporidium parvum is usually considered the agent of human cryptosporidiosis. However, only in the last few years, molecular biology-based methods have allowed the identification of Cryptosporidium species and genotypes, and only a few data are available from France. In the present work, we collected samples of whole feces from 57 patients from France (11 immunocompetent patients, 35 human immunodeficiency virus [HIV]-infected patients, 11 immunocompromised but non-HIV-infected patients) in whom Cryptosporidium oocysts were recognized by clinical laboratories. A fragment of the Cryptosporidium 18S rRNA gene encompassing the hypervariable region was amplified by PCR and sequenced. The results revealed that the majority of the patients were infected with cattle (29 of 57) or human (18 of 57) genotypes of Cryptosporidium parvum. However, a number of immunocompromised patients were infected with C. meleagridis (3 of 57), C. felis (6 of 57), or a new genotype of C. muris (1 of 57). This is the first report of the last three species of Cryptosporidium in humans in France. These results indicate that immunocompromised individuals are susceptible to a wide range of Cryptosporidium species and genotypes.